Aberrations Causing Neurovascular Damage in the Anterior Maxilla during Dental Implant Placement - Shane J. J. McCrea (Hindawi Limited, 2017)
When dental implants are being considered for placement in the maxillary central incisor region, proximity to the nasopalatine canal and its contents needs to be accounted for. The morphology of the canal changes with age. The availability of CBCT has allowed the in-depth analysis of this important variable anatomy. However, an associated important anatomical structure can be easily overlooked: the "canalis sinuosus." This is a neurovascular canal carrying the anterior superior alveolar (ASA) nerve and artery. CBCT frequently shows the canalis sinuosus (CS) as a wide canal lateral to the nasal cavity and also under the anterior part of the nasal floor in close proximity to the NPC. The CS distributes both neural supply and vascular supply to the maxillary anterior teeth which on CBCT sagittal analysis are seen as very fine circular canals having nondistinct walls. The author presents a case history of dental implant placement in the anterior maxilla which resulted in neurovascular disturbance as a result of invasion of the nasopalatine duct and injury to its contents together with the unidentified injury to an aberrant well-defined neurovascular canal inferior to the canalis sinuosus.